Curriculum Transformation Strategy Through Digital Literacy Integration to Enhance Religious Moderation Among Students - Deri Furna Al Haq (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2026)
The transformation of religious curricula in the era of disruption is imperative to address the challenges of low digital literacy and rising religious exclusivism triggered by social media algorithms. Current curricula, which tend to be text-heavy and dogmatic, fail to equip students with information filtering skills, leaving them vulnerable to digital intolerance narratives. Employing a qualitative policy analysis methodology with William N. Dunn’s scoring criteria, this work evaluates various regulatory alternatives to strengthen religious moderation. The analysis reveals that integrating digital literacy into religious education content standards significantly enhances students' cognitive resilience against hoaxes and cyber provocations. The discussion emphasizes the importance of a curriculum pruning strategy to provide space for critical analysis competencies and digital ethics among educators through the TPACK framework. It is concluded that a top-down policy via Ministry of Religious Affairs Regulations is the most effective step in restructuring the educational paradigm. It is recommended that the Ministry of Religious Affairs immediately issue integrated digital literacy regulations and strengthen cross-sectoral collaboration with telecommunications authorities to ensure the successful implementation of inclusive religious moderation in cyberspace.